Innovations in Electronic Control Units: Enhancing Performance and Reliability with AI (International Journal of Engineering and Computer Science, 2024)
Electronic control units (ECUs) are the backbone of any automotive system. These computer systems have a range of functions, such as determining the air-to-fuel ratio, ignition timing, and idle speed for a just-started or driven vehicle. Having played these roles over the decades, today's automotive world is quite different, with a greater focus on getting from Point A to Point B with fuel efficiency, minimal vehicle operation, connectivity, user comfort, and minimal maintenance. It is the ECUs' responsibility to make this exploration comfortable, efficient, safe, and high-tech. Ensuring all this in an ECU-equipped vehicle requires the ECU to be quick, efficient, maintenance-free for some time, and more reliable. To complement these functions, today's ECUs must be more accurate, robust, capable of learning-driven optimization, AI-based capabilities, signals that help predict component life and determine vehicle operation parameters, and low-power and low-cost computational model architectures that handle these functions in real time. The main components that are subject to various types of environmental conditions are connected to the ECU.In recent years, the automotive world has hit some high spots, such as autonomously operated vehicles, AI system-operating vehicles, and other intelligent and high-efficiency hardware operating vehicles. All these high-tech features have a great influence on the ECU's capabilities. In the present work, a range of existing and modern capabilities, features, technologies, ECU architectures, diagnostic methods, trends, and additional improvement suggestions based on requirements are briefly presented. The proposed suggestions are aimed at enhancing ECU capabilities and realizing the use of deep learning and AI in an ECU without losing the real-time, highly accurate data to be processed. High-technology sensors and methods to have influential data for ECU operations in real-time to process data are also presented. The regulatory requirements of specific countries for safer vehicle operation and to have a highly efficient and emission-free world for moving ahead are the spark for this research.